THE ADVANTAGES AND DISADVANTAGES OF INCLUSIVE EDUCATION FROM THE PERSPECTIVE OF FUTURE TEACHERS - Margevica-Grinberga, Ieva; Šūmane, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In Latvia, inclusive education is relevant as seen in the past several decades, during which time society has developed a more comprehensive understanding of and made significant progress towards implementing inclusive education. Nevertheless, there is still a gap between the priorities of education policy and reality in educational institutions. The quality of education accorded to students is informed by the knowledge, understanding and experience of teachers in the implementation of concepts of inclusive education. The current study aimed at identifying the visions of prospective teachers (already working in schools) concerning inclusive education. To explore the experiences of future teachers, this qualitative study used narratives (i.e., written answers to open-ended discussion questions) of prospective teachers as a research strategy. The study team recruited participants at the University of Latvia, which included 61 students in the work-based teacher education study programme and 46 future pre-school and primary school teachers. Therefore, the current study offers insight into how comprehensive education is implemented in Latvian schools. The results reveal a positive attitude on the concept of inclusive education among most prospective teachers. However, they have concerns about the quality of its implementation, which come as a consequence of limited resources (human, time and financial) and the underdeveloped teachers’ professional competence in the implementation of diversity solutions. Therefore, improving the study process of future teachers enhances the development of their competencies in the provision and promotion of solutions regarding inclusive education.